114k views
0 votes
What is the recursive formula when given the explicit formula for thefollowing geometric sequence?2n = 12(33)^-1O A. a₁ = 12, a = -33an-1OB. a₁ = 12, a = 33an-1OC. a₁ = 33, an = 12am-1OD. a₁ = 33, a = -12am-1

What is the recursive formula when given the explicit formula for thefollowing geometric-example-1
User Max Himes
by
4.9k points

1 Answer

3 votes

Given that the explicit formula for GP is


a_n=12(33)^(n-1)

Explanation -

The general explicit formula for GP is


\begin{gathered} a_n=ar^(n-1) \\ where\text{ a=first term and r = common ratio} \end{gathered}

and the recursive formula for that GP is given as


a_n=a_(n-1)* r

Comparing the general formula with the given explicit formula we have


a=12\text{ and r = 33}

So the required recursive formula will be a


a_n=33* a_(n-1)

So option B is correct.

The final answers are, the first term is a = 12 and the recursive formula is
a_n=33a_(n-1)

User Andrepcg
by
4.8k points